Analysis of radiation-induced small Cu particle cluster formation in aqueous CuCl2 - Jayanetti, J. K. D. S.; Mayanovic, Robert A. (My University, 2001)
Synchrotron x-ray radiation is being used extensively as a structure probe to investigate the coordination environment and thus gain insight into the ion–water and ion–ion interactions in aqueous solutions. However, under favorable conditions, there may be instances where the incident x-ray beam can induce oxidation and/or reduction in the solution, thus altering its chemistry. Successive x-ray absorption fine structure spectra, measured in the fluorescence mode from a 55 ppm Cu in CuCl2 aqueous solution, show the formation of copper clusters and their growth as a function of time of irradiation. Initially, the clusters have a nearest neighbor distance of 2.4860.02 Å which, with increase in time of irradiation, increases to 2.5560.01 Å, indicating that the clusters approach the lattice dimensions of bulk copper. Similarly, the Debye–Waller factor of the copper clusters is found to increase by ;50%–55% over the range of time of irradiation. Analysis of spectra measured in the intermediate time period shows signal contributions from a mixture of clusters that can be represented by a mixture of a small cluster ~5–10 Å across! and bulk copper. The nearest neighbor coordination number is found to increase in a manner consistent with the decrease in the surface to volume ratio as the average cluster size approaches its bulk dimensions. The initiation of cluster growth occurs through agglomeration of copper atoms that possibly react to form dimers upon reaction. The copper ions in the solution are reduced to the metallic state by reacting with hydrated electrons produced as a result of radiolysis of water by the incident x-ray beam.